Adsorption and thermal evolution of SO2 on the Pt(110) surface - Zebisch, P.; Stichler, M.; Trischberger, P.; Weinelt, M.; Steinrück, Hans-Peter (Surface Science, 1997)
The adsorption and thermal evolution of SO on a Pt(110) surface was studied by temperature programmed desorption, angle-resolved UV photoelectron spectroscopy and X-ray photoelectron spectroscopy. At 140 K two molecular SO species are observed that are attributed to adsorption on different adsorption sites. Upon heating to 340 K atomic S and molecular SO and SO are formed with the amount of the various products depending on the initial SO coverage. For high SO coverages these reactions are accompanied by molecular SO desorption. The SO species decomposes upon further heating to 500 K leading to SO desorption. SO, which is only formed for high initial SO coverages, is stable up to this temperature but decomposes upon further heating to 650 K. In the same temperature range atomic sulphur and oxygen recombine to desorb as SO.